Ethics and Architectural Drawings: A Framework for Discussion - Ermiyagil, Seyit; Hurol, Yonca (Taylor and Francis, 2021)
The intersection between architecture and ethics has resulted in fruitful debates, but the specific ethical concerns posed by architectural drawings have seldom been explored. This paper presents a quantitative analysis of observations made about architectural drawings that were submitted for a case in North Cyprus and a qualitative analysis of discussions conducted with 15 architects. These observations were made with reference to applied ethical theories and codes of conduct to validate the existence of perceived ethical problems with the drawings. The views expressed by the architects revealed a need for the introduction of new rules and regulations concerning the ethical issues posed by architectural drawings since such issues could, if left unresolved, harm the integrity of the profession.
The intersection between architecture and ethics has resulted in fruitful debates, but the specific ethical concerns posed by architectural drawings have seldom been explored. This paper presents a quantitative analysis of observations made about architectural drawings that were submitted for a case in North Cyprus and a qualitative analysis of discussions conducted with 15 architects. These observations were made with reference to applied ethical theories and codes of conduct to validate the existence of perceived ethical problems with the drawings. The views expressed by the architects revealed a need for the introduction of new rules and regulations concerning the ethical issues posed by architectural drawings since such issues could, if left unresolved, harm the integrity of the profession.
Keywords: applied ethics; architectural drawing; code of conduct; architectural competition; sales catalogues; inconsistency; misleading promise; readability; error